Influence of micronized salt and high-power ultrasound on the quality of beef burgers - Contreras Castillo, Carmen Josefina (2023)
The study aimed to evaluate the combined use of ultrasound (US) and incorporation of micronized salt (MS) as a strategy for reducing sodium without affecting the quality of beef burgers. Ten treatments were manufactured with varying MS content (0.75 %, 1.0 %, and 1.5 %) and ultrasound time (0, 5, and 10 min), with a control treatment manufactured at 1.5 % of regular salt without ultrasound. The beef burgers formulated with 0.75 % MS submitted to the US for 10 min (M0.75US10) reduced the salt content by 50 %, thereby efficiently maintaining texture profile (hardness, springiness, cohesiveness, and chewiness) and decreasing the cooking loss and diameter reduction compared to the control treatment. M0.75US10 treatment also preserved the color of samples after cooking, keeping myoglobin stable. Therefore, micronized salt coupled with ultrasound technology reduces sodium chloride content in beef burgers, enabling the application of clean technology to reduce sodium content in meat products efficiently.